An Analysis of the Altria-Juul Labs Deal: Antitrust and Population Health Implications. (23rd January 2021) - Levy, David T; Sánchez-Romero, Luz María; Douglas, Clifford E; Sweanor, David T
Abstract: On December 19, 2018, Altria announced an offer of 12.8 billion for Juul Labs, combining the largest U.S. cigarette manufacturer with the largest U.S. e-cigarette company. This deal is currently being challenged by the Federal Trade Commission (FTC). We consider the antitrust implications. We also consider population health implications, which we argue are essential to a comprehensive analysis of the impact on consumers. Although the FTC antitrust investigation has focused on closed vaping systems, we argue that the relevant market is the broader nicotine delivery product market, which includes all vaping products along with tobacco products. With Altria having a large market share in the key nicotine delivery product submarkets and with important entry barriers, the merger potentially places Altria in a dominant position in the relevant market. In particular, competition in the vaping submarket is reduced, thereby likely to reduce the availability of less harmful alternatives to cigarettes.